Elements and types of sentences in the context of syntax in reşat nuri güntekin’s novel yeşil gece - Yıldırım, Nilüfer; Boz, Mustafa (Ahmet BURAN, 2024)
Language and culture are two important elements that ensure the formation and continuation of national identity. It is the language that transmits culture to future generations. The elements that make up a language are its sound system, structural features, syntax and vocabulary. Syntax is especially important in terms of showing the style and use of language by poets and writers who create art using that language. In this context, artists who work with language both reveal how they use the language in a literary sense and pass on the characteristics of the language to future generations through the literary works they create. In this respect, syntax studies are of great importance. Reşat Nuri Güntekin is one of our important writers who has contributed to Turkish with his use of language, style and syntax features in his works. In this article, certain sections of Reşat Nuri Güntekin's novel “Yeşil Gece” were examined in terms of sentence elements and sentence types. The sentences examined were classified according to their elements and types. The aim of the study is to determine Reşat Nuri Güntekin's use of sentences. From this point on, the sentence elements and sentence types used in the novel will reflect the artist's style and help determine his power of using Turkish.

Dil ve kültür, millî kimliğin oluşmasını ve devam etmesini sağlayan iki önemli unsurdur. Kültürü gelecek nesillere aktaran dildir. Bir dili oluşturan unsurlar o dile ait ses sistemi, yapı özellikleri, söz dizimi ve söz varlığıdır. Söz dizimi özellikle o dili kullanarak sanat yapan şair ve yazarların üslubunu, dili kullanış biçimini göstermesi bakımından önemlidir. Bu bağlamda dili işleyen sanatçılar hem dili edebî anlamda nasıl kullandıklarını gözler önüne sererler hem de meydana getirdikleri edebî eserler aracılığıyla dil özelliklerini sonraki nesillere aktarırlar. Bu bakımdan söz dizimi çalışmaları büyük önem taşımaktadır. Reşat Nuri Güntekin de dili kullanım şekli, eserlerindeki üslubu ve söz dizimi özellikleriyle Türkçeye katkı sağlamış önemli yazarlarımızdan biridir. Makalede Reşat Nuri Güntekin’in “Yeşil Gece” adlı romanının belli bölümleri cümlenin ögeleri ve cümle türleri bakımından incelenmiştir. İncelenen cümleler, ögelerine ve türlerine göre sınıflandırılmıştır. Çalışmanın amacı Reşat Nuri Güntekin’in cümleleri kullanış biçimini belirlemektir. Bu noktadan hareketle romanda kullanılan cümlenin ögeleri ve cümle türleri sanatçının üslubunu yansıtacak, Türkçeyi kullanma gücünü belirlemeye yardımcı olacaktır.
SÖZ DİZİMİ BAĞLAMINDA REŞAT NURİ GÜNTEKİN’İN YEŞİL GECE ROMANINDA CÜMLENİN ÖGELERİ VE CÜMLE TÜRLERİ
Keywords: Linguistic Structures (Incl. Phonology; Morphology and Syntax); Dilsel Yapılar (Fonoloji; Morfoloji ve Sözdizimi dahil)